The Effect of Plyometric Hurdle Training on the Vertical Jump of Volleyball Extracurricular Students - Lukas Adi Wira Mohamad Zain; Fajar Syamsudin (Universitas Negeri Semarang, 2026)
Vertical jump ability is one of the key components of volleyball, especially for executing successful smashes and blocks. Based on observations at SMP Negeri 1 Jambu, the vertical jump ability of students in the volleyball extracurricular program is still not optimal, and the training provided has not specifically focused on improving lower-body explosive power. This study aimed to determine the effect of plyometric hurdle jump training on the vertical jump ability of students in the volleyball extracurricular program at SMP Negeri 1 Jambu. This study employed an experimental method with a one-group pretest-posttest design. The sample consisted of 13 students selected through purposive sampling. The research instrument was a vertical jump test. The plyometric hurdle jump training program was conducted over 12 sessions, three times a week. Data were analyzed using a normality test and a paired-sample t-test. The results showed that the average vertical jump increased from 52.85 cm in the pretest to 59.31 cm in the posttest, an increase of 6.46 cm. The statistical analysis yielded a significance value of 0.000 (p < 0.05). Therefore, plyometric hurdle jump training significantly improved the vertical jump ability of students in the volleyball extracurricular program at SMP Negeri 1 Jambu.